1997
DOI: 10.1021/jp970994o
|View full text |Cite
|
Sign up to set email alerts
|

Product Branching Ratios of the NH2(X2B1) + NO2 Reaction

Abstract: The reaction of NH2(X2B1) with NO2 was studied at 298 K using time-resolved infrared diode laser spectroscopy to detect N2O and NO products. The N2O + H2O channel was confirmed to be a rather minor contribution to the overall reaction, with a branching ratio of 0.24 ± 0.04. The branching ratio of the NO + H2NO channel was measured to be 0.76 ± 0.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Park and Lin (1997) studied the reaction over the temperature range from 300 to 900 K and reported ktotal = 8.1 x 1016T-I.44exp(-135/T) cm 3 mol-1 s-l , with the N20 channel being 19% of the total, independent of temperature. This branching ratio is consistent with the results of Lindholm and Hershberger (1997), who reported a branching ratio of 24% to N20 and H20, 76% to NH20 and NO. In contrast, extrapolation of the Glarborg et al result to 300 K predicts 77% for the N20 channel.…”
Section: Reactions Ofn02supporting
confidence: 92%
“…Park and Lin (1997) studied the reaction over the temperature range from 300 to 900 K and reported ktotal = 8.1 x 1016T-I.44exp(-135/T) cm 3 mol-1 s-l , with the N20 channel being 19% of the total, independent of temperature. This branching ratio is consistent with the results of Lindholm and Hershberger (1997), who reported a branching ratio of 24% to N20 and H20, 76% to NH20 and NO. In contrast, extrapolation of the Glarborg et al result to 300 K predicts 77% for the N20 channel.…”
Section: Reactions Ofn02supporting
confidence: 92%
“…More recent model calculations by Kohlmann and Poppe [1999] adopted a re-measured value of 60% for the branching ratio [Meunier et al, 1996], which -together with a number of other revisions -gave an estimated N 2 O source of only 0.2 Tg N a À1 . Other studies report even lower branching ratios [Lindholm and Hershberger, 1997;Park and Lin, 1996] [Michalski et al, 2003], the contribution of the NH 2 + NO 2 source is likely to be at the higher end of the estimate here, because D 17 O(NO 2 ) is expected to be between 0.9 and 1.5 times D 17 O(HNO 3 ), depending on the formation pathway (hydrocarbon oxidation by NO 3 , heterogeneous hydrolysis of N 2 O 5 or gas-phase reaction of NO 2 + OH).…”
Section: Reaction Of Nh 2 + Nomentioning
confidence: 87%
“…More recent model calculations by Kohlmann and Poppe [1999] adopted a re-measured value of 60% for the branching ratio [Meunier et al, 1996], which -together with a number of other revisions -gave an estimated N 2 O source of only 0.2 Tg N a À1 . Other studies report even lower branching ratios [Lindholm and Hershberger, 1997;Park and Lin, 1996] of 19 to 24% which have led IUPAC to recommend a value of (25 ± 15)% (IUPAC Subcommittee on Gas Kinetic Data Evaluation: Data Sheet NOx22, http://www.iupac-kinetic.ch.cam.ac.uk). Here, we scale the estimated source strength of 0.2 Tg N a -1 from Kohlmann and Poppe [1999] to the recommended branching ratios and thus obtain a range for the source strength of 0.03 to 0.13 Tg N a À1 .…”
Section: Reaction Of Nh 2 + Nomentioning
confidence: 99%
“…Values for both the overall rate constant and the branching fraction β, defined as k 1a /( k 1a + k 1b ), ,, have been reported over a wide range of conditions, but the scatter in the data is considerable. Measurements of the overall rate constant vary by an order of magnitude at 500 K. ,, In addition, there appears to be some inconsistency in the low and high temperature measurements of the rate constant, with the recent high temperature data of Song et al being substantially greater than expected from a simple extrapolation of the low temperature data.…”
Section: Introductionmentioning
confidence: 99%
“…presumed that these pathways were unconnected. Incorporation of this saddle point in a master equation analysis suggests that H 2 NO + NO are the only products, whereas a variety of experimental studies have indicated that the branching to the N 2 O + H 2 O channel is 20% or more. ,, The study of Sun et al has ruled out the branching to a number of other possible channels. In the present work, the NH 2 + NO 2 reaction has been studied experimentally using laser photolysis/laser-induced fluorescence (LIF) and theoretically with high level ab initio transition state theory based master equation methods.…”
Section: Introductionmentioning
confidence: 99%